PENGARUH GAME EDUKATIF TERHADAP KEMAMPUAN PEMBELAJARAN SISWA AKUNTANSI KELAS X SMK Negeri 1 KEDAWUNG KOTA CIREBON - Anisa Riva Anggraeni (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine how the effect of educational games on the accounting learning ability of class X students of SMK Negeri 1 Kedawung. This type of research uses a quasi-experimental design. This research was conducted with all students of class X Accounting institutions and finance (AKL) 3 as the control class and X Accounting institutions and finance (AKL) 2 as the experimental class. This data analysis technique uses normality test, homogeneity test, hypothesis testing, paired t test, and t test. The results stated that student learning outcomes for the cognitive domain in the control class obtained an average posttest score of 83.39. In the experimental class, the average value of the posttest results was 82.53 so that it was smaller than the average value in the control class. So it can be concluded that the use of educational game-based learning media is very sufficient with student learning outcomes so that during accounting subjects as interactive media. Keywords: learning media, Quizizz, and Learning outcomes.